Integrating Ludruk Art Culture in Elementary Pancasila Education: A Needs Analysis - Chusniyah, Nafidatul; Setyowati, Raden Roro Nanik; Puspita, Ari Metalin Ika; Solihin, Annas (Journal of Innovation and Research in Primary Education, 2025)
Learning Pancasila Education in elementary schools has an important role in instilling national values from an early age. However, in practice, this learning is still dominated by conventional methods that do not associate the material with the local culture. One of the cultural potentials that can be integrated into learning is the art of ludruk, which is full of Pancasila values such as mutual cooperation, deliberation, and justice. This study aims to analyze the need for the development of textbooks based on ludruk culture to increase the effectiveness of Pancasila Education learning in elementary schools. This study uses a qualitative method with data collection techniques through in-depth interviews, participatory observations, and documentation studies. The research was conducted at SDN Tambak Wedi 508 Surabaya with 2 Pancasila Education teachers, 1 principal, and 40 students from grades IV and V as participants. The results of the study show that learning is still centered on standard textbooks without the integration of local culture. Teachers face limitations in relevant teaching materials, while students have difficulty understanding the values of Pancasila concretely. However, observations indicate that student engagement significantly improves when ludruk cultural elements are introduced, especially in discussions related to mutual cooperation and justice. In conclusion, the development of ludruk-based textbooks is very necessary to increase students' understanding of Pancasila values while preserving local culture. The recommended textbook should be contextual, interactive, and designed as a supplemental resource that aligns with the current elementary curriculum.